Characterization of paneth cells in alpacas (Vicugna pacos, Mammalia, Camelidae) - Vasquez, María (2016)
Paneth cells are secretory epithelial cells of the innate immune system of the intestine of several mammals, including alpacas. Little is known about the latter; thus, in the present study we described the morphology and histochemical characteristics of Paneth cells in healthy fetuses, and young and adult alpacas. For this purpose, samples of duodenum, jejunum and ileum were taken from 6 fetuses at different days of pregnancy (between days 221-330), 66 offsprings (between 0 and 45-days-old) and 5 adult alpacas (>2-years-old). Samples were fixed in 10% buffered formalin and processed for histological and morphometrical analysis using HE and Masson Trichomics technique. Immunohistochemistry was used to identify Paneth cells using anti-lysozyme antibody. In addition, the lectinhistochemichal binding-pattern of Paneth celĺs granules was evaluated. Lyzozyme was immunohistochemically detected in the granules of Paneth cells from day 283 of pregnancy in all the small intestinal sections of the studied fetuses. In newborn alpacas Paneth cells were initially found in the duodenum, but the following days (days 18-21 after birth) they were also found in the ileum. Their size gradually increased after birth, but then no significant differences were found. In adult alpacas the number was lower than offsprings. We suggest that Paneth cells early differentiate in the small intestine of alpacas, and the increase in their number during the first two weeks of life strongly support their possible involvement in the intestinal defensive functions against the enteric diseases that occur during the lactancy stage.